CONSIDERACOES SOBRE OS FATORES COADJUVANTES DOS MECANISMOS DE OCLUSAO E FACILITACAO CARDIAL. ESTUDO COMPARATIVO - Orsi, A. M.; Ferreira, A. L. (My University, 1975)
The morphological factors that should work to help the cardial continence (oesophageal and gastric mucosal folds) and are arranged to cooperate for the cardial opening (smooth muscle fibres of the longitudinal layer of oesophagus and stomach) are described in the opossum, comparatively to the man. Also comparatively discussed are the anatomical disposition of diaphragm, oesophageal hiatus of diaphragm, gastrophrenic ligament and phrenoesophageal membrane.
Considerations on coadjuvant factors of cardial closure and facilitation mechanisms. Comparative study